SPORTS AND TEHNICAL EDUCATION FOR TZHE STUDENTS OF TEACHING FACULTY - Goran Šekeljić; Milovan Stamatović; Žana Bojović; Živorad Marković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
The aim of this study was to examine the effects of physical education after primary and secondary education. An assessment of sports-technical education in the basic elements of gymnastics, volleyball and basketball was conducted on the sample of 104 students of the Faculty of Education in Uzice. The results indicate that about 80% of evaluated motor skills were performed error-free or with only minor errors in technique and posture, 15% of those covered by the survey performed the required elements with significant errors in technique and posture, and only a few percent do not have these skills. This means that the quality of teaching in primary and secondary schools, as far as men are concerned ,was such as to meet one of the main goals of education - the acquisition of basic sports and technical education. The results are significant because in this case it is about the students who will teach physical education to children of junior school age, and survey results indicate that they will be able to demonstrate the basic elements of gymnastics and sports games correctly.